2015
DOI: 10.1186/s13148-015-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation of genes involved in fibrosis progression in non-alcoholic fatty liver disease and alcoholic liver disease

Abstract: BackgroundChronic liver injury can lead to the development of liver fibrosis and cirrhosis but only in a minority of patients. Currently, it is not clear which factors determine progression to fibrosis. We investigated whether DNA\methylation profile as determined by pyrosequencing can distinguish patients with mild from those with advanced/severe fibrosis in non-alcoholic liver disease (NAFLD) and alcoholic liver disease (ALD). To this end, paraffin-embedded liver biopsies were collected from patients with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 25 publications
2
122
0
3
Order By: Relevance
“…Abnormal methylation of the PNPLA3 promoter was associated with fibrosis severity in a large number of Japanese people 100 . Differences in the methylation status at specific CpG islands within the promoter of anti-fibrogenic (PPARA and PPARD) and pro-fibrogenic (TGFB1, COL1A1 and PDGFA) genes might have a prognostic value in differentiating patients with mild fibrosis from those with advanced fibrosis 101 .…”
Section: [H2] Epigeneticsmentioning
confidence: 99%
“…Abnormal methylation of the PNPLA3 promoter was associated with fibrosis severity in a large number of Japanese people 100 . Differences in the methylation status at specific CpG islands within the promoter of anti-fibrogenic (PPARA and PPARD) and pro-fibrogenic (TGFB1, COL1A1 and PDGFA) genes might have a prognostic value in differentiating patients with mild fibrosis from those with advanced fibrosis 101 .…”
Section: [H2] Epigeneticsmentioning
confidence: 99%
“…10 So far, the most studied epigenetic mechanisms related to NAFLD in humans are the microRNA serum/plasma profile and DNA methylation. 10,11 In human liver, very few studies have demonstrated the importance of DNA methylation in NAFLD, [12][13][14][15] from which only 2 have applied a genome-wide (GW) approach. 13,14 However, none of these GW studies have carefully explored the relation between differential methylation and clinical parameters related to NASH.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that DM-CpG methylation patterns in background liver were most significantly associated with aging in NBNC patients, followed by the presence or the absence of diabetes mellitus, whereas fibrosis, alcohol intake and degree of BMI did not affect background methylation difference. Previous studies suggested that fibrosis and alcohol intake could affect DNA methylation of the liver tissues [29,30]. Due to obesity as well as alcohol intake, NAFLD could increase oxidative stress and DNA damage in hepatocytes; therefore, it is conceivable that both NAFLD and alcohol intake might contribute to hepatocarcinogenesis via the same epigenetic pathway, which would lead to a lack of difference in the methylation profile within the background liver tissues, regardless of the fibrosis stage.…”
Section: Discussionmentioning
confidence: 99%